Editors' Introduction - C H (Critical Hermeneutics, 2019)
Through this choral tribute to Domenico Jervolino we hope to have reconstructed the breadth of his philosophical interests, his theoretical lines but above all the bonds of friendship and esteem that over the years have intertwined-in high Ricoeurian style-between several Italian and International figures. For this reason, this is a ‘choral’ remembrance and homage, a way of witnessing the esteem towards the scholar with whom interest and reflections have been shared over the years, in the conviction that to germinate them, they need to be share and participated among those who have a common vocation. A vocation (and the interest towards a reflection) that seeks in History, in Psychoanalysis, in the texts, places where to meet men and try to build together “shared worlds”, for others to inherit, within an infinite thread of interpretations.